Comparative genomics of Mortierella elongata and its bacterial endosymbiont Mycoavidus cysteinexigens. (1st February 2017) - Uehling, J.; Gryganskyi, A.; Hameed, K.; Tschaplinski, T.; Misztal, P. K.; Wu, S.; Desirò, A.; Vande Pol, N.; Du, Z.; Zienkiewicz, A.; Zienkiewicz, K.; Morin, E.; et al.
Summary: Endosymbiosis of bacteria by eukaryotes is a defining feature of cellular evolution. In addition to well‐known bacterial origins for mitochondria and chloroplasts, multiple origins of bacterial endosymbiosis are known within the cells of diverse animals, plants and fungi. Early‐diverging lineages of terrestrial fungi harbor endosymbiotic bacteria belonging to the Burkholderiaceae. We sequenced the metagenome of the soil‐inhabiting fungus Mortierella elongata and assembled the complete circular chromosome of its endosymbiont, Mycoavidus cysteinexigens, which we place within a lineage of endofungal symbionts that are sister clade to Burkholderia . The genome of M. elongata strain AG77 features a core set of primary metabolic pathways for degradation of simple carbohydrates and lipid biosynthesis, while the M. cysteinexigens (AG77) genome is reduced in size and function. Experiments using antibiotics to cure the endobacterium from the host demonstrate that the fungal host metabolism is highly modulated by presence/absence of M. cysteinexigens . Independent comparative phylogenomic analyses of fungal and bacterial genomes are consistent with an ancient origin for M. elongata – M. cysteinexigens symbiosis, most likely over 350 million years ago and concomitant with the terrestrialization of Earth and diversification of land fungi and plants.